2015
DOI: 10.1093/cjres/rsu032
|View full text |Cite
|
Sign up to set email alerts
|

High growth firms, jobs and peripheral regions: the case of Scotland

Abstract: Abstract.High growth firms (HGFs) are expected to be a major source of job creation during the economic recovery. This has prompted a shift in enterprise policy in many countries away from supporting start- to have a high propensity to be acquired, increasing their susceptibility to head office closure. The paper suggests that the tendency towards 'policy universalism' in the sphere of entrepreneurship policy is problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…This is evident in the fact some locations see more start-ups scale up into larger businesses, large-scale exits and high levels of IPOs (Coutu, 2014). In some regions with low entrepreneurial cultures, many promising start-ups and HGFs become sold off prematurely (Mason et al, 2015;Spigel, 2015). 4 Even the majority of the lauded Israeli start-up population end up being acquired by US firms (Senor and Singer, 2009).…”
Section: Entrepreneurial Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This is evident in the fact some locations see more start-ups scale up into larger businesses, large-scale exits and high levels of IPOs (Coutu, 2014). In some regions with low entrepreneurial cultures, many promising start-ups and HGFs become sold off prematurely (Mason et al, 2015;Spigel, 2015). 4 Even the majority of the lauded Israeli start-up population end up being acquired by US firms (Senor and Singer, 2009).…”
Section: Entrepreneurial Culturementioning
confidence: 99%
“…For example, many are geographically centred in one location and are based around a core cluster or clusters of related industrial activities like the oil and gas industry in Calgary (Spigel, 2015). Indeed, work in Scotland found that nearly a third of Scottish HGFs relied on the oil and gas sector for the majority of their revenue (Mason et al, 2015). This sectoral dependency clearly makes some of these firms heavily dependent on a cyclical resource.…”
Section: Conceptualising Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…Pike examined the role of local institutions and governance in shaping regional resilience [38]. The role of other factors, such as location and the presence of high growth firms have been examined as well [39,40].…”
Section: Determinants Of Regional Resiliencementioning
confidence: 99%
“…Moreover, enterprise policy in the UK has been conceived nationally with little sensitivity to local contexts (Huggins and Williams 2011), and consequently achieved little in reducing spatial and socio-economic disparities (Gardiner et al 2013). Indeed, there has in fact been a widening of the divide between core and peripheral economic places (Mason et al 2015), not only at the interregional but also intraregional level. This highlights the necessarily heterogeneous local responses in adapting to shocks.…”
Section: Introductionmentioning
confidence: 99%